A comparative study of topical tacrolimus and topical triamcinolone acetonide in nodular scabies. Issue 6 (27th July 2020) - Manjhi, Mukesh; Yadav, Pravesh; Mohan, Sneha; Sonthalia, Sidharth; Ramesh, V.; Kashyap, Varun
Abstract: The aim of this study was to compare the efficacy and safety of 0.1% triamcinolone acetonide and 0.03% tacrolimus ointment for the treatment of nodular lesions of scabies. In this double‐blind randomized controlled trial, 50 Indian men with postscabeitic persistent nodular lesions (labelled to have nodular scabies (NS)/postscabies prurigo (PSP)) over the external genitalia, were enrolled. They were randomized into two groups to receive either a mid‐potency topical corticosteroid (TCS); triamcinolone acetonide 0.1% ointment twice daily, or topical calcineurin inhibitor (CNI); tacrolimus ointment 0.03% twice daily over the nodular lesions for 2 weeks. All patients were followed up on three visits: 1, 2, and 6 weeks, for assessment. Efficacy was evaluated by 5‐point range investigator‐assessed VAS, and a 4‐point severity of pruritus scale (SPS) score. The mean VAS score was higher in triamcinolone group compared to tacrolimus group at both follow‐ups, although statistically significant only at 2nd week visit. The fall in mean SPS at both follow‐ups was also higher in the steroid group, but the difference was not statistically significant. While, the overall tolerance to either ointment was excellent, mild hypopigmentation, and epidermal atrophy were detected on dermoscopic evaluation of the treated areas at the 2nd week visit in a small subset of patients in the triamcinolone group. The frequency of relapse of lesions and/or pruritus after four weeks of the 2‐week therapy was high in both the groups (higher in tarolimus group). Conclusively, although both treatment options provided safe and satisfactory short term improvement, the results from this study suggest an overall higher efficacy of a mid‐potency TCS like triamcinolone 0.1% over topical CNI like tacrolimus 0.03%, in the short‐term treatment of nodular lesions of NS/PSP. Topical CNIs may be considered for maintenance of effect, if prolonged therapy is warranted.